Risk of dental caries at Child Development Centers in Riobamba, Ecuador - Tipán Masapanta, Daniel Eduardo (2023)
Objective. To determine the caries risk of the Child Development Centers (CDI) of the program of linkage with society of the Dental Career of the National University of Chimborazo (Ecuador). Methods. This study was observational and descriptive. The study population was 200 infants and, by means of inclusion and exclusion criteria, was reduced to 143 infants. The data collection instruments were the clinical histories of the ICD database, which obtained a value in the Cariogram Reduced program. Finally, statistical tests were  erformed in SPSS and Excel. Results. The data showed that 52% of the sample had a relatively low risk of caries. As the infant develops through the stages of development, the predisposition to caries risk will increase, with no major difference according to gender. The real probability of avoiding new carious lesions in the study sample was 68% and each of the IDCs acquired different percentages, as far as the other caries risk models are concerned. Conclusions. The relatively low caries risk presents high percentages; while the one with the lowest percentage is the high risk.